Skull Meningioma Associated with Intradural Cyst: A Case Report. Issue 10 (1st November 2017) - Mouri, Genshin; Suzuki, Hidenori; Hatazaki, Seiji; Matsubara, Toshio; Taki, Waro
We present the first report of intraosseous meningioma accompanied by intradural cyst formation. A 76-year-old woman had previously undergone breast cancer treatment, so the preoperative diagnosis was metastatic breast cancer. This case reminds us that the possibility of meningioma should be kept in mind in patients with breast cancer, irrespective of neuroimaging findings.